2017
DOI: 10.1177/2167702617741381
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Victimization and Early-Adult Psychopathology: Approaching Causal Inference Using a Longitudinal Twin Study to Rule Out Noncausal Explanations

Abstract: Adolescence is the peak age for both victimization and mental disorder onset. Previous research has reported associations between victimization exposure and many psychiatric conditions. However, causality remains controversial. Within the Environmental Risk Longitudinal Twin Study, we tested whether seven types of adolescent victimization increased risk of multiple psychiatric conditions and approached causal inference by systematically ruling out noncausal explanations. Longitudinal within-individual analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
126
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 140 publications
(155 citation statements)
references
References 93 publications
26
126
0
3
Order By: Relevance
“…However, we used reliable, valid, and age-appropriate methods to assesses victimization, and exposed cases in our cohort were known to have endured severe experiences. Moreover, the victimization experiences we analyzed predict poor psychiatric outcomes strongly in this cohort (3), attesting that it is possible to detect stress-related consequences of victimization using this study’s victimization measures. Specifically, victimization was followed by increases in mental health problems over a childhood previctimization baseline of emotional/behavioral problems, and discordant-twin analyses showed that victimization predicted an increased risk of mental health problems independently of family background and genetic risk.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, we used reliable, valid, and age-appropriate methods to assesses victimization, and exposed cases in our cohort were known to have endured severe experiences. Moreover, the victimization experiences we analyzed predict poor psychiatric outcomes strongly in this cohort (3), attesting that it is possible to detect stress-related consequences of victimization using this study’s victimization measures. Specifically, victimization was followed by increases in mental health problems over a childhood previctimization baseline of emotional/behavioral problems, and discordant-twin analyses showed that victimization predicted an increased risk of mental health problems independently of family background and genetic risk.…”
Section: Discussionmentioning
confidence: 72%
“…Early-life stress is thought to cause many adverse health outcomes, including altered brain development (1), compromised cognitive functioning (2), poor mental health (3), and multiple physical illnesses (4). Perhaps the most pressing question at the nexus of neurobiology and public health is how stress “gets under the skin” to bring about these pleiotropic effects (59).…”
mentioning
confidence: 99%
“…Over the past century, there has been tremendous progress in understanding childhood trauma (Danese & McCrory, ). Despite this progress, traumatised children still often have poor long‐term outcomes, struggling with education and employment (Jaffee et al, ) and developing psychopathology that is complex (Schaefer et al, ), treatment‐resistant (Nanni, Uher, & Danese, ) and thus recurrent throughout the life course (Agnew‐Blais & Danese, ; Nanni et al, ). Novel research paradigms are needed to make transformative changes in the life of these children.…”
Section: Introductionmentioning
confidence: 99%
“…Across various academic disciplines, scholars have uncovered relationships between youth violent victimization and several behavioral, health, and social consequences later in life (Foster & Brooks-Gunn, 2009;Hanson, Sawyer, Begle, & Hubel, 2010;McDougall & Vaillancourt, 2015). Problems such as depression, substance abuse, crime and violence, and low educational attainment are all disproportionately found among adults who were victimized in adolescence (Macmillan & Hagan, 2004;Schaefer et al, 2018;Turanovic & Pratt, 2015). Violent victimization is therefore considered an adverse life event that disrupts healthy youth development across a wide range of life domains (D'Andrea, Ford, Stolbach, Spinazzola, & van der Kolk, 2012;Margolin, Vickerman, Oliver, & Gordis, 2010;van der Kolk, Roth, Pelcovitz, Sunday, & Spinazzola, 2005)-it can violate a youth's sense of safety and control, lead to distressing flashbacks, and can take a toll on brain structure and function (Anda et al, 2006;Bremner, 2006;Lupien, McEwen, Gunnar, & Heim, 2009).…”
Section: Introductionmentioning
confidence: 99%